Book of Bosh - Edward Lear; Brian Alderson (London Penguin, 1993)
This is a collection of lyrics and prose aiming to display a wide range of bosh, both known and lesser known. As well as limericks and nonsense songs, there are "eggstrax" from Edward Lear's letters and a dictionary of his "wurbal inwentions".
Keywords: storybook